Uniform estimates of attracting sets of extended Lurie systems using LMIs - Martins, Andre C. P.; Alberto, Luis F. C.; Bretas, Newton G. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This research presents a systematic procedure to obtain estimates, via extended Lyapunov functions, of attracting sets of a class of nonlinear systems, as well as an estimate of their stability regions. The considered class of nonlinear systems, called in this note the extended Lurie system, consists of nonlinear systems like those of the Lurie problem where one of the nonlinear functions can violate the sector conditions of the Lurie problem around the origin. In case of nonautonomous systems the concept of absolute stability is extended and uniform estimates of the attracting set are obtained. Two classical nonlinear systems, the forced duffing equation and the Van der Pol system, are analyzed with the proposed procedure.
Keywords: attracting sets; linear matrix inequality (LMI); Lurie problem; Lyapunov methods; nonlinear systems